PEMAKNAAN PERJUANGAN PEREMPUAN DI SOCIAL MEDIA(STUDI KASUS ARTIKEL “IBU, 10 TAHUN PENJARA, 10 MILYARRUPIAH” DI DALAM BLOG WWW.ALANDAKARIZA.COM) - Suciati, Pijar (Jurnal Vokasi Indonesia, 2015)
This study, in general aimed to describe and know the meaning of the message women struggle by users of social media (Facebook and Twitter) to the blog article of Alanda Kariza. This study uses a critical paradigm of constructionism. The type is descriptive research using case study strategy. Data collection techniques used is by interview (interview), with the selection of informants using purposive judgmental convenience. The conclusion that can be drawn from this research is, in the end a meaning that appears in the mind of the reader to a blog written in social media is influenced by many things, including the background of the blog readers. Whether it's family background, educational background, ideology embraced, blog writing style and choice of words. Similarly, the meaning of which is trying to be revealed in this study, namely the meaning of the struggles of women was also influenced by the above factors. According to Stuart Hall, there are three kinds of readings / interpretations of the text, namely (meaning dominant / hegemonic code, negotiated meaning / code, oppositional decoding / code). All three appeared in this study.